REFLECTIONS ON HIDDEN VOICES IN THE EFL CLASSROOM: THE “ANXIOUS” LEARNER AND THE “CARING” TEACHER - Mouhoubi-Messadh, Chahrazad (PEOPLE: International Journal of Social Sciences, 2017)
A number of research studies have attempted to investigate the major learning-teaching complexities of EFL classrooms. The role of affect in general, and language anxiety in particular received considerable attention in educational research. For most teachers, it is likely challenging to put theories of affect in learning into practice. That challenge stems from the fact that every educational setting is unique of its own complexities. Specifically, the anxious language learner might have difficulties in verbalizing his or her thoughts in class. Some learners would decide not to contribute in class and keep their “hidden voices” inaudible for a long time. As such, the aim of this paper is to share and provide tentative reflections on the anxious learner in the classroom relying on self-reports and teachers’ discussions. A first step is based on describing possible signs of language anxiety, and what learners say about themselves. The subsequent point is devoted to the“caring” teacher’s role (s) in helping anxious learners overcome hindrances of anxiety in an EFL educational setting. It is important to note that most descriptions given stem from the Algerian university context.